PENGARUH STRATEGI PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI SDN 09 KABA WETAN - Ahmad Abdul Rochim; Siti Bandiah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The accuracy in choosing a learning strategy is a very important part in efforts to improve the achievement of student learning outcomes. Therefore this study aims to determine the effect of learning strategies on mathematics learning outcomes. This study uses a 2x2 factorial design research. Through this design the effects of Interactive learning strategies and problem-based learning will be compared to student mathematics learning outcomes. The population in this study were all students of grade IV SDN 09 Kaba Wetan, totaling 76 students, consisting of 2 classes. To determine the sample class, a random sampling technique is used. The sample classes used were 2 classes totaling 76 students, class IV-A as an Interactive class and class IV-B as a problem-based class. The data analysis technique used is descriptive and inferential statistical techniques. And testing the analysis requirements is the normality test using the Lilifors Test, while the homogeneity requirements are using the F Test and Barlett Test. After testing the analysis requirements, the two-way variance analysis of Analilsis is performed. The results of this study indicate that there is an interaction effect between learning strategies on student mathematics learning outcomes. So that the selection of appropriate learning strategies is influenced by the ability of teachers to understand the characteristics of their students. In the learning strategy applied by the teacher can optimize student mathematics learning outcomes by choosing class strategies namely Interactive learning and problem based learning classes.